Biosorpsi Logam Berat Timbal (Pb) menggunakan Biomassa Bakteri Asam Laktat Lokal Riau - Bernadeta Leni Febriarti; Nuria Puspita Sari; Rafika Fatzuarni (Universitas Sebelas Maret, 2018)
Lead is a heavy metal that is highly toxic, detectable to all inanimate objects in the environment and throughout biological systems. The purpose of this study is to test the biosorption capability of Lactic Acid Bacteria (BAL) of Riau against heavy metal Lead (Pb). Biosorption test is conducted with Grow BAL SB3 and SB6 on MRS broth medium with Pb concentration of 5, 10 and 50 ppm.Previously made growth curve to know the optimum growth time and the best incubation time. biosorption was done by measuring Pb which was absorbed by AAS (Automathic Absorption Sphectrofotometer). The result showed that isolate BAL SB3 able to absorb Pb at concentration 5, 10 d 50 ppm with biosorption efficiency 46,6%, 36,8% and 30,7% . Whereas SB6 with biosorption efficiency is 44,8%, 32,2% and 25,7%